PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI KEUANGAN DASAR - Tria Aprilia, - (2018)
Penelitianinidilakukan di SMK PGRI 2 Cimahi, dengantujuanuntukmengetahuiapakahadaperbedaanhasilbelajarsiswa yang menerapkan model pembelajarankooperatiftipeStudent Teams Achievement Division(STAD) denganhasilbelajarsiswa yang tidakmenerapkan model pembelajarankooperatiftipeStudent Teams AchievementDivision (STAD) padamatapelajaranAkuntansiKeuanganDasar di SMK PGRI 2 cimahi, dengansampelpenelitianyaitukelas X Akuntansi 1 sebagaikelaskontroldan X Akuntansi 3 sebagaikelaseksperimen. Teknikpengambilansampeldilakukandenganmenggunakanpurposive sampling. Desainpenelitian yang digunakanadalahpenelitiankuantitatif, menggunakanmetodeQuasi EksperimendenganPost test Only Control Design. Pengujian data menggunakanujinormalitasdenganmenggunakanrumusChi Kuadrat, ujihomegenitasdenganmenggunakanUjifdanUjihipotesisdenganmenggunakanUji-t. Hasilpenelitianmenunjukanbahwapenerapan model STAD secaraumumberlangsungefektif. HasilpengujianhipotesisdenganmenggunakanUji-t menunjukanbahwanilait_hitung adalah sebesar 4,035 dan nilai t_tabel dengan α=0,05 adalah 1,998. Karenat_hitung>t_tabel , makahasilbelajarsiswa yang menerapkan model pembelajarankooperatiftipeStudent Teams Achievement Division (STAD) lebihtinggidaripadahasilbelajarsiswa yang tidakmenerapkan model pembelajarankooperatiftipeStudent Teams AchievementDivision (STAD). Denganadanyaperbedaantersebutdapatdisimpulkanbahwapenerapan model pembelajaran STAD berpengaruhterhadaphasilbelajarsiswapadamatapelajaranAkuntansiKeuanganDasar;---This research was conducted at SMK PGRI 2 Cimahi, with the aim to find out whether there is a difference in student learning outcomes that apply the cooperative learning model of type Student Teams Achievement Division (STAD) and the learning outcomes of students who do not apply cooperative learning model of type Student Teams Achievement Division (STAD) in basic financial Accounting subjects in SMK PGRI 2 Cimahi, with a sample of research is class X class 1 as Accounting controls and X 3 as the Accounting classroom experiments. The technique of sampling done by using purposive sampling. The research design used is a quantitative research method using Quasi, experiments with Post test Only Control Design. Test data using the test of normality by using the Chi Quadrat, homegenitas test using Test-f and test the hypothesis by using Test-t. Results of the study showed that application of the model of STAD in General take place effectively. The results of hypothesis testing using t-Test showed that the value of tstatistic is 4.035 and ttabelwith α = 0.05 is 1.998. Because tstatistic>ttabel, then the results of the learning of students who are applying cooperative learning model of type Student Teams Achievement Division (STAD) is higher than the results of a study of students who do not apply the cooperative learning model of type Student Teams Achievement Division (STAD). With the difference that it can be concluded that the application of the model of learning effect on learning outcomes STAD students on basic financial Accounting subjects